Image guidance used for large joint and bursa injections; a survey study. Issue 2 (2nd April 2020) - Cushman, Daniel M.; Christiansen, Jacob; Kirk, Melissa; Clements, Nathan D.; Cunningham, Shellie; Teramoto, Masaru; McCormick, Zachary L.
ABSTRACT: Objectives: To determine the current rates of use of available image guidance modalities for large joint and bursal injections, in addition to their relationships to physician demographics. Methods: An electronic survey was sent to 3, 400 members of the American Medical Society for Sports Medicine (AMSSM), examining types of guidance used for each large joint and bursal injection. Results: A total of 674 sports medicine physicians responded to the survey. Intra-articular hip and glenohumeral joint injections were more commonly performed with ultrasound guidance, while palpation-guidance was more common with all other injections. Physicians who specialized in Physical Medicine & Rehabilitation (PM&R) were more likely to use ultrasound for trochanteric bursa (p = 0.007, OR = 4.16 [1.46–11.8]), while internal medicine-, pediatrics-, and family medicine-trained physicians were more likely to use palpation guidance for at least one joint (p < 0.05). Physicians with fewer years of experience were more likely to use ultrasound for glenohumeral joint injections (p ≤ 0.002 for all age groups with less than 20 years of experience, ORs ranging from 6.3 to 9.2). Conclusion: Palpation-guidance is the most common technique used for large joint and bursal injections, other than for glenohumeral and hip joint injections. PM&R-trained physicians and those with less experience tend to use ultrasound more frequently.